PENGARUH MODEL PEMBELAJARAN TEAM ASSITED INDIVIDUALIZATION TERHADAP HASIL BELAJAR IPAS KELAS V DI MIN 4 BANDAR LAMPUNG - Rifka Maulia Putri; Chairul Amriyah; Yuli Yanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the Team Assisted Individualization (TAI) model on the science learning outcomes of fifth-grade students at MIN 4 Bandar Lampung with a focus on analytical skills (C4). The study used a quasi-experimental design with two classes (VA and VB, each with 20 students) selected through purposive sampling. The instrument was a multiple-choice test with 30 items, and 20 of them were declared valid and reliable (α = 0.847). The data were normally distributed and homogeneous, so they were analyzed using an independent samples t-test. The results showed a significant difference between the experimental class (mean = 86.75) and the control class (mean = 79.75) with t(38) = −2.121 and p = 0.040. The increase in the achievement of the C4 indicator indicates the effectiveness of TAI in developing students' analytical skills. These findings recommend the implementation of TAI in Madrasah Ibtidaiyah as a collaborative learning strategy that supports the implementation of the Independent Curriculum.